Тактичні особливості проведення огляду місця події в умовах ведення бойових дій - Корнієнко, В.В.; Korniienko, V.V.; Савчук, Т. І.; Savchuk, T. I. (Вісник Кримінологічної асоціації України. – 2023. – № 2 (29). – С. 167-179, 2023)
Стаття присвячена криміналістичному аналізу тактики проведення огляду місця події та інших першочергових дій слідчо-оперативної групи в умовах бойових дій. Зокрема, розглянуто тактичні особливості пошуку та фіксації слідів вибухів, та пов’язаних з ним руйнувань об’єктів, питання залучення спеціалістів та використання спеціальної техніки.

The article represents the tactics of the crime scene management and preliminary inspection of the incident of rocket attacks, explosions, destructions of civil infrastructure facilities, including death bodies. Authors conducted an overall review of modern problematic aspects of the first response police team which investigate crimes and misdemeanors in a places of military fighting. The research is focus on tactic of investigation`s inspection of criminal events, search and collecting evidences, fixing traces, video recording of the progress and results of the investigative action, pictures, scene scratches, 3D scanning, involving specialists and the use of special equipment and other criminal procedures.

Статья посвящена криминалистическому анализу тактики проведения осмотра места происшествия и других первоочередных действий следственно-оперативной группы в условиях боевых действий. В частности, рассмотрены тактические особенности поиска и фиксации следов взрывов и связанных с ним разрушений объектов, вопросы привлечение специалистов и использование специальной техники.
Tactical features of inspection of criminal events in a places of the combat operations
Keywords: огляд місця події; inspection of the scene; осмотр места происшествия; документування воєнних злочинів; documenting war crimes; документирование военных преступлений; умови бойових дій; conditions of hostilities; условия боевых действий; тактичні особливості огляду; tactical features of the review; тактические особенности осмотра; криміналістична техніка; forensic technique; криминалистическая техника